Подарки из бумаги - Ращупкина Светлана Юрьевна (Азбука рукоделия, 2010)
Экземпляры: М/а ДБ (20110316) / Инвентарный номер: 96975 / Цена: 115.00 / Сис.шифр: 37.248 / Авт.знак: Р 28 / ГРНТИ: 75.35 / ББК: 37.24